Civilian’s Contributions and the Management of Health-Related Issues in the Nigerian Military during the Nigerian Civil War, 1967-1970 - Ali, Hannatu K. (NIU Journal of Humanities, 2026)
This work looks at the Nigerian federal military government's medical outsourcing during the Nigerian Civil War as a way to complement its medically challenged logistics. Thus, it pays attention to civilians’ contributions on health-related issues during the Nigerian Civil War, 1967-1970, which contributed to winning the war strategy. Salient aspect put forward by the paper includes services of paid and volunteer health workers from the Medical School of the University of Ibadan, who diagnose, cure and rehabilitate injured and sick soldiers to complement the overwhelmed medical corps of the Nigerian Army. The paper utilises historical and analytical methods to interpret primary and secondary sources. By implication, it posits that the civilian services sustained the war for it prolong period, most especially interrupted civilian blood donation and transfusion to the injured soldiers on the front lines. Such civilian services were motivated by international organisations such as the Nigerian Red Cross, which assisted Military Hospitals, visiting the wounded soldiers, holding prayer sessions with victims and distributing gifts of biscuits and other provisions to the wounded soldiers. Nigerians offer spiritual therapy coordinated by Gideon International Organisation; The Jama’atul Nasril Islam under the Grand Khadi of Northern Nigeria and Sheikh Abubakar Mahmud Gumi, augment and complement the health logistics of the Nigerian military, which improves its combat effectiveness. It gives hope to the wounded and sick veterans as they feel some people are there for them and improve their spiritual, psychological and emotional well-being. It contributes to scholarship on Nigeria's Civil War Win-the War efforts. Keywords: Win-the-War, Spiritual therapy, War Support and war pharmaceutical